The Burning Maze (The Trials of Apollo Book 3) - Rick Riordan (USA PENGUIN, 2019)
The third book in the latest series from international bestselling author, Rick Riordan He was a God once. Until he was cast out his father, Zeus. Now, he's an awkward teenager. Called Lester. The only way out is a series of scary and dangerous trials, of course. For his third trial, Apollo must journey through the Labyrinth to free an Oracle who only speaks in puzzles. Then, defeat the most vicious of three very vicious Roman Emperors. (All without the use of his godly powers.) It looks like he will need all the help he can get - from some new and old friends. __________ This edition includes a Percy Jackson short story! Clarisse, daughter of Ares, the Greek god of war, needs Percy Jackson's help. Her father's chariot has been stolen and she has to get it back by sunset. The only hitch? The chariot-jackers are none other than her terrifying immortal brothers Phobos and Deimos. Can Percy and Clarisse get the chariot back before it's too late? Find out in, Percy Jackson and the Stolen Chariot __________ More books by Rick Riordan: The Percy Jackson series: Percy Jackson and the Lightning Thief Percy Jackson and the Sea of Monsters Percy Jackson and the Titan's Curse Percy Jackson and the Battle of the Labyrinth Percy Jackson and the Last Olympian Percy Jackson: The Demigod Files The Heroes of Olympus series: The Lost Hero The Son Of Neptune The Mark of Athena The Heroes of Olympus: The Demigod Files The Kane Chronicles series: The Red Pyramid The Throne of Fire The Serpent's Shadow The Magnus Chase Series: Magnus Chase and the Sword of Summer Magnus Chase and the Hammer of Thor Magnus Chase and the Ship of the Dead